Effects of different boiling processes on chemical compositions of Lilii Bulbus soup - He, Guowei; Liu, Ziying; Chen, Hong; Wang, Yuhui; Huang, Wei; Lu, Xiangyang; Tian, Yun; Liu, Huhu (Frontiers in Nutrition, 2022)
Lilii Bulbus, an edible Chinese herbal medicine, has a long history in medicine. However, research on effectively boiling Lilii Bulbus is rare. To make the more nutritious Lilii Bulbus soup, the optimized boiling process, using an alternate heating mode by decoction pot carrying a mixture of water and Chinese liquor at the ration of 9:1, was established in this study. Compared to the soup prepared by the daily process, the polysaccharide amount improved by 54%, and the total heavy metals decreased by 33.5% using the optimized boiling process. In addition, the total saponins at 34.3 μg/g were determined in the soup prepared by the optimized process. Meanwhile, the colchicine content in the boiled Lilii Bulbus soup was undetectable using the optimized process. This research performs an optimized boiling process for making Lilii Bulbus soup, and provides a reference for generating high commercial value from Lilii Bulbus soup in the future.